Scarecrow Educational Tourism Management Training for Staf Candidates at Plantation Area - Pamuji, Wirawan; Suyanto; Nun Jamianto (PT FORMOSA CENDEKIA GLOBAL, 2024)
Plantation Area with pest distractions are merely distinguished with animals and plants, the plants are destructed observation by farmer search of the matter because it clings on the body of flowers or planted fruits, animals can appear suddenly in surprise, as it requires scarecrow to expel them all. The Research applies Descriptive Qualitative Methods in training Students at University as worker candidates at field working area to manage the plantation in beneficences. Due that Field at Plantation Area is potentially disturbed by such omnivore animals, scarecrow are functioned to harass the pest in controlling high volume of pests and scarecrow to harass the disturbing animals at once to function it as Educational Tourism for School Students with all levels to train them how to function scarecrow in unique forms for expelling Plant Disturbing Animals